A recyclable indole-based polymer for trinitrotoluene adsorption via the synergistic effect of dipole–π and donor–acceptor interactions. Issue 34 (31st July 2019) - Wang, Yan; Zhang, Lin; Yang, Li; Ma, Yuanchi; Chang, Guanjun
Abstract : A new type of indole-based porous organic polymer with amine units (PAIN) has been constructed, which possesses encouraging and effective adsorption properties for trinitrotoluene by taking advantage of the synergistic effect of dipole–π and donor–acceptor interactions. Abstract : A new type of indole-based porous organic polymer with amine units (PAIN) has been constructed, which possesses encouraging and effective adsorption properties for trinitrotoluene by taking advantage of the synergistic effect of dipole–π and donor–acceptor interactions.